Trabecular microbypass stent implantation in pseudoexfoliative glaucoma: long-term results. Issue 9 (September 2020) - Ferguson, Tanner J.; Swan, Russell J.; Bleeker, Adam; Dockter, Zachary; Karpuk, Kayla L.; Schweitzer, Justin; Ibach, Mitch; Berdahl, John P.
Abstract : Retrospective study with 5-year outcomes evaluating the iStent trabecular microbypass stent with phacoemulsification in PXG showed that the procedure provides a sustained reduction in IOP up to 5 years postoperative. Abstract : Purpose: To evaluate the long-term safety and efficacy of an iStent trabecular microbypass stent in combination with cataract surgery in pseudoexfoliative glaucoma (PXG). Setting: Private practice, Sioux Falls, South Dakota, USA. Design: Retrospective, consecutive case series. Methods: Eyes with a preoperative diagnosis of PXG implanted with a single iStent trabecular microbypass stent with concomitant cataract surgery were included. Performance outcome measures included intraocular pressure (IOP) and number of glaucoma medications. Safety outcomes included intraoperative or postoperative complications and the need for secondary procedures. Results: The series included 117 eyes. IOP was reduced by 25% to 15.3 ± 3.7 mm Hg at 5 years postoperatively from 20.5 ± 6.6 mm Hg at baseline. The statistically significant ( P < .01) 36% reduction in medication use through 36 months was not sustained, and medication use was unchanged from baseline (1.4 ± 1.0) at 5 years postoperatively (1.3 ± 1.1) ( P > .05). At 5 years, 52% of eyes had an IOP of 15 mm Hg or lesser, increased from 22% at baseline. There were no severe postoperative complications; 5 eyes (4%) underwent an additional glaucoma procedure. Conclusions: Implantation of a trabecular microbypass stent with concomitant cataract surgery provided a sustained reduction in IOP up to 5 years postoperatively. The long-term safety profile of the device in this population was excellent with a low rate of postoperative IOP spikes and low percentage of eyes undergoing a secondary procedure.